SURGICAL APPROACHES TO PRIMARY AND METASTATIC LIVER NEOPLASMS - Starzl, Thomas E. (1976)
Providing the anatomic conditions are appropriate, removal of as much as 85–90% of the liver is a relatively safe technique for the treatment of benign or malignant primary hepatic tumors and of isolated hepatic metastases. There have been apparent cures of malignant disease by this approach, but the paucity of concentrated experience at any one center and the failure so far to pool data from different centers effectively make a valid prognosis impossible. Total hepatectomy and liver replacement has resulted in the apparent core of some patients with primary hepatic malignancy. However, there has been an extremely high rate of recurrence of tumor. Small cancers which are lethal because of their strategic locations may provide an unusually good indication for liver replacement. Liver transplantation would rarely, if ever, be indicated for metastases to the liver.